1982
DOI: 10.1126/science.216.4546.630
|View full text |Cite
|
Sign up to set email alerts
|

Venus Was Wet: A Measurement of the Ratio of Deuterium to Hydrogen

Abstract: The deuterium-hydrogen abundance ratio in the Venus atmosphere was measured while the inlets to the Pioneer Venus large probe mass spectrometer were coated with sulfuric acid from Venus' clouds. The ratio is (1.6 +/- 0.2) x 10(-2). The hundredfold enrichment of deuterium means that at least 0.3 percent of a terrestrial ocean was outgassed on Venus, but is consistent with a much greater production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
209
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(223 citation statements)
references
References 12 publications
10
209
0
Order By: Relevance
“…However, the atmosphere of Venus currently has about 100,000 times less water than the oceans and atmosphere of the Earth and is strongly enriched in deuterium. The measurements on Venus give D/H = 150 ± 30 (Donahue et al 1982;de Bergh et al 2006) and up to 240 ± 25 of the terrestrial value. This suggests that Venus lost most of its water at some time in the past.…”
Section: Greenhouse Effect and Climate Evolutionmentioning
confidence: 99%
“…However, the atmosphere of Venus currently has about 100,000 times less water than the oceans and atmosphere of the Earth and is strongly enriched in deuterium. The measurements on Venus give D/H = 150 ± 30 (Donahue et al 1982;de Bergh et al 2006) and up to 240 ± 25 of the terrestrial value. This suggests that Venus lost most of its water at some time in the past.…”
Section: Greenhouse Effect and Climate Evolutionmentioning
confidence: 99%
“…Evidence that the atmosphere of Venus has lost most of its water (assuming it had acquired a large quantity) came from the Pioneer Venus measurements of the d/h ratio, which is about 100 times the terrestrial value [McElroy et al, 1982;Donahue et al, 1982] and has been confirmed by Earthbased spectroscopy [de Bergh et al, 1991]. This implies that Venus has likely lost at least the equivalent of 100 times more water than its present reservoir.…”
Section: Atmospheric Chemistry and Atmospheric Evolutionmentioning
confidence: 93%
“…Two results were of particular importance to geology. One was the discovery by one of the probes of the so-called deuterium anomaly, a D/H ratio larger by a factor of 150 than it is in Earth's oceans [Donahue et al, 1982]. This implies significant hydrogen escape from the planet, suggesting that early in its history Venus could have lost a large amount of water [e.g., Donahue and Russel, 1997].…”
Section: History Of Venus Explorationmentioning
confidence: 99%